Penguatan Kapasitas Generasi Muda Melalui Pelatihan Bahasa Inggris Pemandu Wisata Dusun Putak, Kutai Kartanegara. - Indriani, Novita; Musdalifah; Sabalius Uhai; Heldina Pristanti (EDUTOURISM Journal Of Tourism Research, 2024)
English language training at Dusun Putak Village, Loa Duri Ilir Village, Kutai Kartanegara, provides a platform for local tour guides to improve their English communication skills and competence. This form of the program has been designed to provide participants with relevant vocabulary, phrases, and communication techniques in the context of tourism guidance by merging theoretical conceptualization with role-play simulation and non-tes evaluation. More than language competencies, it also develops interpersonal and customer-servicing skills to provide a rewarding tourism experience for foreign tourists. Proficient communication in the English language facilitates the delivery of more interesting information to the tourist guide and simultaneously promotes locals' sustainable local tourism. This training is expected to improve the quality of tourist guide services and encourage the younger generation of Dusun Putak to promote the pot actively.